(untitled) (Journal of Nepal Geological Society, 2019)
Disasters every year proclaim life of thousands and destruct infrastructures worth billions worldwide. Moreover, the developing countries are more prone to hazards as they are found to be lagging in early preparedness regarding the consequences of disaster. Nepal, in the wake of the 7.8 magnitude 2015 Gorkha Earthquake had to face devastating effects as the country lost nearly ten-thousand lives and structures accounting 6.69 billion US (NRA, 2016). Private Housing, one of the subordinates of social sector, faced the colossal damage, making the dwellers bound to take shelter under the makeshift tents. To that end, government has adopted owner driven approach for reconstruction and it is advancing in an amplified way. Since the rural terrains with low strength masonry had to face shattering effects, the reconstruction demands their construction with incorporation of seismic resistant components. The technique of construction since significantly differs than the primitive way, diverse modes of assistance is required by house owners to make their buildings codal compliant, which is also linked with obtaining subsidy. Not only reconstruction is a technical process, rather it is also a blend of economic, social and cross cutting issues. Having said that, the paper aims to study a multidimensional approach of socio-technical assistance (STA) through the study of different cases of ongoing post-earthquake reconstruction. The paper studies the impacts of socio-technical assistance being provided at various earthquake affected areas to understand what aspects of socio-technical assistance are aiding in the current reconstruction process. In conclusion, the paper identifies the core areas of sociotechnical assistance that is required in the aftermath of a disaster and how the current institutional structure can be modified to enhance the quality of socio-technical assistance being provided through various government and non-government agencies.